A Comparative Study between Type-1 and Type-2 Fuzzy Logic Controllers for 4-Leg Active Power Filter - Mohamed M. El-Sotouhy, Ahmed A. Mansour, Mostafa I. Marei, Aziza M. Zaki, Ahmed A. El-Sattar (International Journal of Control and Automation, 2020)
The four-leg active power filter is used in many applications to improve the level of network efficiency and reduce the rates of unwanted signals (Harmonics) that produces from unbalanced and non-linear loads. These signals negatively affect the performance of the network and increase the losses of the network. Among those active filters that are used four-leg active power filter. It was used in this paper instead of a 3-wire active power filter as it enables the control of each phase separately and also helps to control the neutral current as well. Many controllers that are used to control four-leg inverter of which is traditional as Hysteresis current controller, PI- controller, etc.... and there are some intelligent techniques such as neural networks, and fuzzy logic controller type1 and type 2. In this paper, both types of fuzzy logic controllers are used and compared based on the Matlab/simulation results. Comparison is based on the total harmonics distortion (THD) percentage for the current of the network and the DC-link voltage control. The results of the simulation proved type 2 is more efficient than type1.